1992
DOI: 10.1002/hlca.19920750704
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanisms of Enantioselective Reactions Using α,α,α′,α′ ‐Tetraaryl‐1,3‐dioxolane‐4,5‐dimethanol(TADDOL)‐Derived Titanates: Differences between C2‐ and C1‐symmetrical TADDOLs – facts, implications and generalizations

Abstract: The titanates derived from C(,C(,LY ',ol'-tetraaryl-l,3-dioxolane-4,5-dimethanols (TADDOLs, prepared from tartrate) act as catalysts for enantioselective additions of dialkylzinc compounds to aldehydes. For the standard reaction chosen for this investigation of the mechanism, the addition of diethylzinc to benzaldehyde, there is very little change of selectivity with different aryl substituents on the TADDOLate ligands (Tables 2 4 , examples). With 0.02 to 0.2 equiv. of the chiral titanates, selectivities abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
109
1
10

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(124 citation statements)
references
References 112 publications
4
109
1
10
Order By: Relevance
“…It has been suggested repeatedly that the chirality of the phosphane backbone is transmitted to the substrate through the face ± edge [48] or quasi-equatorial array [49] of phenyl groups. Certain quadrants around the metal center become more sterically hindered than others, forcing the prochiral substrate into a certain conformation leading to chiral induction.…”
Section: Rhmentioning
confidence: 99%
“…It has been suggested repeatedly that the chirality of the phosphane backbone is transmitted to the substrate through the face ± edge [48] or quasi-equatorial array [49] of phenyl groups. Certain quadrants around the metal center become more sterically hindered than others, forcing the prochiral substrate into a certain conformation leading to chiral induction.…”
Section: Rhmentioning
confidence: 99%
“…[11] Moreover, the BINOL and the TADDOL systems gave quite different complexes depending on the Ti:diol ratios. [5,6] The fact that resonances of only one type of BODOL unit was observed implied that the complex had a high symmetry. The two non-equivalent isopropyl group signals indicated that we were examining a single complex, and not an average signal from multiple complexes.…”
Section: Resultsmentioning
confidence: 97%
“…In this case the structure was shown to be a monomeric Ti-diolate of composition [(TADDOLate)Ti(OiPr) 2 ] (Figure 1c). [6] It should be noted that the structure and composition of the complexes formed are strongly dependent on the diol to [Ti(OiPr) 4 ] ratio used on mixing the components. In this report we will focus on the 1:1 complexes, which do not contain halogens or semihydrated alcoholates.…”
Section: Introductionmentioning
confidence: 99%
“…Seebach et al 20 tested the enantioselectivity of the intermolecular MPV of the TADDOL ligand. The TADDOLzirconate complex 6 (Scheme 6) (equimolar amount) dissolved in i-PrOH (0.06 M) catalyzed an enantioselective MPV reduction of acetophenone.…”
mentioning
confidence: 99%